Tabletop imaging using 266nm femtosecond laser pulses, for characterization of structural evolution in, single molecule, chemical reactions. (August 2015) - Ibrahim, Heide; Wales, Benji; Beaulieu, Samuel; Schmidt, Bruno E; Thiré, Nicolas; Bisson, Éric; Hebeisen, Christoph T; Wanie, Vincent; Giguére, Mathieu; Kieffer, Jean-Claude; Spanner, Michael; Bandrauk, André D; et al.
Synopsis: We have demonstrated a generally applicable tabletop approach utilizing a 266nm femtosecond laser pulse pump, 800nm pulse probe, coupled with Coulomb explosion imaging (CEI). We have investigated two simple chemical reactions in C2 H2 + simultaneously: proton transfer and C=C bond-breaking, triggered by multiphoton ionization to excited states. Too and fro proton migration results are in excellent agreement with new ab initio trajectory simulations which predict isomerization timescales and pathways.